Genetic diagnosis of familial hypercholesterolaemia using a rapid biochip array assay for 40 common LDLR, APOB and PCSK9 mutations. (November 2016) - Martin, Rosalind; Latten, Mark; Hart, Padraig; Murray, Helena; Bailie, Deborah A.; Crockard, Martin; Lamont, John; Fitzgerald, Peter; Graham, Colin A.
Abstract: Background and aims: Familial hypercholesterolaemia (FH) leads to a lifelong increase in plasma LDL levels with subsequent increase in premature vascular disease. Early diagnosis and treatment is the key to effective management of this condition. This research aims to produce a simple and cost effective genetic test which could identify the majority (71%) of mutations causing FH in the UK and Ireland. Methods: The Randox Biochip Array Technology was used to detect 40 point mutations in LDLR, APOB and PCSK9 genes, over two 5 × 5 arrays. This technology uses multiplex allele specific PCR and biochip array hybridisation, followed by a chemiluminescence detection system and software for automated mutation calling. Results: The FH biochip array assay was validated in the Belfast Genetics Laboratory using 199 cascade screening samples previously sequenced for known FH causing family mutations, the overall sensitivity was 98%. The assay was then used for routine testing of 663 patients with possible FH, from clinics across the UK and Ireland. A total of 49 (7.4%) mutation positive individuals were identified, however, for the clinics in England the detection rate was 12.9%. Further analysis of 120 biochip negative patients, using DNA sequencing, did not identify any false negatives. Conclusions: The FH biochip array provides a rapid and reliable genetic test for the majority of FH causing point mutations in the UK and Ireland. A total of 32 samples can be run in 3 h. This allows clinics to evaluate additional patients for a possible diagnosis of FH such as patients with high LDL, patients with early onset coronary disease, and patients with relatives known to have FH. Highlights: The familial hypercholesterolaemia (FH) biochip array detects 40 mutations in the LDLR, APOB and PCSK9 genes. The assay is a rapid and reliable genetic test for FH. This assay will increase the detection of new FH cases and reduce cardiac events.